EFFECT OF NUTRIENT-RICH ALTERNATIVES ON QUALITY OF COMPOST MADE FROM MARKET WASTES (2015)
Globally, chemical fertilizers cause serious environmental pollution and health hazards. Studies have shown that compost, a product of biodegradable organic matter, is not popular among Nigerian farmers because of its low quality. Improving compost quality is a challenge and supplementing it with natural fortifiers may be safer than opting for chemical fertilizers. This study was therefore designed to explore the effect of nutrient-rich alternatives on quality of compost made from market wastes. This was an experimental study design, comprising compost preparation, formulation with natural fortifiers, farm plot experiments and laboratory analyses. Organically Fortified Fertilizers (OFFs) comprised: Plant-Based (PB), Animal-Based (AB), Rock-Based (RB), Organic-mixture (OMmixture of PB, AB and RB), Synthetic/ Chemical (SC) while ordinary compost was used as control. The plot experiment was a simple plot randomised complete block design with three replicates. The main plots comprised three crops- maize (cereal), soybean (legume) and yam (tuber) while five different OFFs at three rates of applications- 2.0 tons, 2.5 tons and 3.0 tons per hectare and control formed subplots. Formulation characteristics [organic-carbon, Total Nitrogen (TN), phosphorus and potassium] were determined using spectrophotometeric and other standard methods. Germination index method was used to assess phytotoxicity of OFFs. Values obtained for phytotoxicity were compared with Thailand Agricultural Commodity and Food Standard of ≥80 for safe OFFs. Effects of OFFs on Agronomic Parameters (APs) [Number of Leaves (NL), Plant Height (PH), Stem Girth (SG), Leaf Area (LA) and crop yield] were assessed in plot experiments. Data were analysed using descriptive statistics and ANOVA at p = 0.05. Chemical analysis of OFFs revealed organic-carbon (%): 33.2±0.0, 38.4±0.2, 27.7±0.1, 34.8±0.0, 28.4±0.2, 32.8±0.21; TN (%): 5.69±0.0, 5.74±0.0, 5.85±0.0, 6.05±0.0, 6.15±0.0, 3.21±0.0, phosphorus (%):0.3±0.0, 0.5±0.0, 0.2±0.0, 0.8±0.0, 0.2±0.0, 0.7±0.1 and potassium (%): 0.5±0.0, 0.7±0.0, 0.4±0.0, 1.0±0.0, 0.4±0.0, 0.9±0.0 for PB, AB, RB, OM, SC and control respectively. The control had significantly higher phosphorus and potassium, and lower TKN than any of the formulations. Values obtained for phyto-toxicity were higher than 80 with exception of SC that was toxic to soybean at 3.0 tons/Ha (74.2). Specifically, OM and RB for maize [NL (10.0±1.1; 9.2±1.0), PH (23.9±5.4cm; 22.7±3.6cm), SG (2.2±0.4cm; 2.2±0.4cm), LA (2.7±0.1cm2; 3.4±0.7cm2)]; AB and RB for soybean [NL (20.3±10.1; 15.3±4.5), PH (12.0±3.5cm; 10.8±5.8cm), SG (0.4±0.1cm; 0.4±0.1 cm), LA (21.0±15.7cm2; 18.7±7.2 cm2)] and RB for yam [PH (44.0±24.0cm); SG (0.8±0.1cm)] respectively gave the best crops’ performances in APs among all the formulations and the control. Rate of application of OFFs showed no significant effects on APs. However, AB at 2.0 tons/ha followed by PB (2.5 tons/ha) gave the highest soybean yield; RB (2.0 tons/ha) gave the highest maize yield and OM (3.0 tons/ha) gave highest yam tuber yield. Nutrient-rich materials sourced from animal, plant and rock changed the chemical composition of compost made from market wastes and yielded better agronomic performances than the synthetic fertilizer. Fortification of compost with natural materials which are readily available and environmentally friendly should be promoted among the farmers.